UPTAKE OF COMMUNITY HEALTH STRATEGY ON SERVICE DELIVERY AND UTILIZATION IN KENYA - Buong Jack Amayo Buong’; Gwoswar Clementine Adhiambo; Dan Owino Kaseje; Hazel Miseda Mumbo; Odhiambo Odera; Mary Evelyn Ayugi (European Scientific Journal, ESJ, 2013)
Great Lakes University of Kisumu developed and tested a Comprehensive Primary Health Care (CPHC) model to facilitate the uptake of essential health services towards Millennium Development Goals (MDGs). The model focused specifically on the principles of intersectoral collaboration, community participation and empowerment to enhance access to health care. A study was undertaken in partnership with the Ministry of Health (MOH) to assess the implementation of the components of the model in different socio-demographic contexts in Kenya, and their relationship with health outcomes. This was a comparative, descriptive study which engaged the end users, policymakers, managers and communities in the design and implementation of research to enhance the utilisation of results. The CPHC intervention elements included: establishment of Community Health Units, governance and linkage structures, training of the health workforce, establishment of Community Based Information system and using it for regular dialogue at community and health facility levels leading to decisions and health actions.Findings showed improvements in governance and management of the health system; service delivery and health outcomes such as immunization coverage, Antenatal Clinic attendance and health facility delivery.